Assessing the Disease Activity in Crohn’s Disease, Nothing Is Enough Alone - Inci, Ismail; Celik, Zeynep Sude; Kani, Haluk Tarık (Turkish Journal of Gastroenterology, 2025)
Cite this article as: Inci I, Celik ZS, Kani HT. Assessing the disease activity in Crohn’s disease, nothing is enough alone. Turk J Gastroenterol. Published online November 3, 2025. doi:10.5152/tjg.2025.25519.